Mutation of a single allele of the cancer susceptibility gene BRCA1 leads to genomic instability in human breast epithelial cells - Konishi, Hiroyuki (National Academy of Sciences, 2011)
Biallelic inactivation of cancer susceptibility gene BRCA1 leads to breast and ovarian carcinogenesis. Paradoxically, BRCA1 deficiency in mice results in early embryonic lethality, and similarly, lack of BRCA1 in human cells is thought to result in cellular lethality in view of BRCA1's essential function. To survive homozygous BRCA1 inactivation during tumorigenesis, precancerous cells must accumulate additional genetic alterations, such as p53 mutations, but this requirement for an extra genetic “hit” contradicts the two-hit theory for the accelerated carcinogenesis associated with familial cancer syndromes. Here, we show that heterozygous BRCA1 inactivation results in genomic instability in nontumorigenic human breast epithelial cells in vitro and in vivo. Using somatic cell gene targeting, we demonstrated that a heterozygous BRCA1 185delAG mutation confers impaired homology-mediated DNA repair and hypersensitivity to genotoxic stress. Heterozygous mutant BRCA1 cell clones also showed a higher degree of gene copy number loss and loss of heterozygosity in SNP array analyses. In BRCA1 heterozygous clones and nontumorigenic breast epithelial tissues from BRCA mutation carriers, FISH revealed elevated genomic instability when compared with their respective controls. Thus, BRCA1 haploinsufficiency may accelerate hereditary breast carcinogenesis by facilitating additional genetic alterations.